2020
DOI: 10.1038/s41419-020-2727-2
|View full text |Cite|
|
Sign up to set email alerts
|

The integrated stress response induces R-loops and hinders replication fork progression

Abstract: The integrated stress response (ISR) allows cells to rapidly shutdown most of their protein synthesis in response to protein misfolding, amino acid deficiency, or virus infection. These stresses trigger the phosphorylation of the translation initiation factor eIF2alpha, which prevents the initiation of translation. Here we show that triggering the ISR drastically reduces the progression of DNA replication forks within 1 h, thus flanking the shutdown of protein synthesis with immediate inhibition of DNA synthes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…DNA fiber analysis. Primary MM and UF cells were labeled with 50 μM IdU (Sigma-Aldrich I-7125) followed by 100 μM CldU (Sigma-Aldrich C-6891) for 30 min each as described previously 57 . UtSM and UtSM-RNaseH expressing cells were treated with 100 nM CCT254515 for 2 h in between Idu and Cldu treatments.…”
Section: Generation Of Stable Rnaseh-expressing Uterine Smooth Muscle...mentioning
confidence: 99%
“…DNA fiber analysis. Primary MM and UF cells were labeled with 50 μM IdU (Sigma-Aldrich I-7125) followed by 100 μM CldU (Sigma-Aldrich C-6891) for 30 min each as described previously 57 . UtSM and UtSM-RNaseH expressing cells were treated with 100 nM CCT254515 for 2 h in between Idu and Cldu treatments.…”
Section: Generation Of Stable Rnaseh-expressing Uterine Smooth Muscle...mentioning
confidence: 99%
“…We then sought to identify the mechanism underlying the elevated levels of RNA:DNA hybrids that we found in MM cells. Recently, it has been demonstrated that the Integrated Stress Response (ISR) induces R‐loops in U2OS cells (Choo et al , 2020). Since a peculiar characteristic of MM cells is a high Unfolded Protein Response (UPR) due to their abnormal production of immunoglobulins (Nikesitch et al , 2018), it is conceivable that this type of stress may contribute to the generation of R‐loops.…”
Section: Resultsmentioning
confidence: 99%
“…TriC is a chaperone complex that assists in protein folding (Knowlton et al, 2021; Martín-Cófreces et al, 2021; Yam et al, 2008) and which has been reported to influence various cellular pathways including gene expression (Shaheen et al, 2021), cellular signalling (Weng et al, 2021), and protection against proteotoxic stress (Llamas et al, 2021). Interestingly, recent data indicate that activation of the integrated stress response, a cellular signalling cascade which responds to protein misfolding, leads to inhibition of histone gene synthesis and consequent formation of R-loops that are known to inhibit DNA RF progression (Choo et al, 2020). Curiously however, published data also show that inhibition of RF progression caused by lack of histone synthesis is not associated with dramatic elevation of RPA-ssDNA (Mejlvang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%